The beauty of belief: decorating the Württemberg church during the reformation - Watson, Róisín (St Andrews studies in reformation history, 2025)
The Beauty of Belief sheds new light on Lutheran relationships with ecclesiastical decoration in southwest Germany following the Duchy of Württemberg’s Reformation in 1534. Based on extensive original archival research and engagement with surviving images and objects, Róisín Watson compellingly demonstrates how Lutherans moved away from initial acts of iconoclasm and towards embracing the possibilities of the religious image in their devotional routines. She explores the interactions of Württemberg rulers, pastors, and congregations with their ecclesiastical spaces across the political upheavals of the sixteenth and seventeenth centuries. In doing so, this book tells not only the story of the visual culture of the Reformation, but an account of Württemberg’s Reformation itself